(untitled) (Stamford Journal of Pharmaceutical Sciences, 2010)
In this work zinc sulfate, ferrous sulfate and ascorbic acid was formulated on the same pellet by combination pelletization technique and their and in vitro dissolution studies were performed by using United States Pharmacopoeia (USP) apparatus type II. In addition, effect of different types of polymers, formulation variables and variations in coating composition on the release of drug were studied. The desired release profile for ferrous sulfate was 35% for 1st hour, 45-75% for 2nd hour and 60-85% for third hour and not less than 85% for 4th hour. The release rate controlling polymer used was various concentrations of Methoccel K15M CR with different concentrations of Microcrystalline cellulose (Avicel PH 101). The maximum release percentage of Ferrous Sulphate was obtained from 2.5 % of Methocel K15M CR and 30 % Avicel PH 101 containing pellets (F-4) and it was 92.32%. And the minimum release percentage of Ferrous Sulphate was obtained from 10 % of Methocel K15M CR and 35.7% Avicel PH 101 containing pellets (F-1) and it was 86.36%. The release profile from other formulations containing 35.4% Methocel K 15M CR & 7.5% Avicel (F-2) and 32% Methocel K 15M CR & 4% Avicel (F-3) were also within desired range. The effect of Eudragit coating (enteric) and the presence of PEG and HPMC in the film coating composition on the drug release were also investigated. Hydrophobic matrix pellets prepared using lower concentrations of Methocel K15M CR were found to be best suited for modulating the delivery of the ferrous sulphate from the combination. Key words: Non Pariel Seeds (NPS); Pan Coater; Ascorbic acid; Methocel K15M CR; Pelletization; PEG; Avicel PH 101; Xanthan gum. DOI: 10.3329/sjps.v2i2.5824 Stamford Journal of Pharmaceutical Sciences Vol.2(2) 2009: 53-58